“LIBASTIK” Free Plastic Environment with Creative Hands - Arifin, Muhammad; Manurung, Lastiur; Muham, Novia Angelia Br; Pohan, Putri Amanda; Alya, Kharisma Rahmadhani; Marpaung, Maria Magdalena; Simatupang, Linda E M; Wandari, Kameilia; Tarigan, Jenni Parlopes Br; Aulia, Ismi; Utami, Mauliddina; Togatorop, Inneke MF (LPPM STIKOM Tunas Bangsa, 2024)
AbstractPlastic waste is a waste that is difficult to decompose by soil. Plastic cannot be recycled and will cause environmental pollution that is detrimental to humans. The plastic that we throw away carelessly can become handicrafts from used goods that make a lot of money. So that UMSU Pre-Service PPG students have an innovation to make collage paintings from this plastic waste which is named the leadership orojeck program entitled